2021
DOI: 10.1109/access.2021.3094723
|View full text |Cite
|
Sign up to set email alerts
|

HGAN: Hyperbolic Generative Adversarial Network

Abstract: Recently, Hyperbolic Spaces in the context of Non-Euclidean Deep Learning have gained popularity because of their ability to represent hierarchical data. We propose that it is possible to take advantage of the hierarchical characteristic present in the images by using hyperbolic neural networks in a GAN architecture. In this study, different configurations using fully connected hyperbolic layers in the GAN, WGAN, CGAN, and the mapping network of the StyleGAN2 are tested in what we call the HGAN, HWGAN, HCGAN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Using the intuition that images are organized hierarchically, several works have proposed hyperbolic generative adversarial networks (GANs). Lazcano et al (2021) propose a hyperbolic GAN which replaces some of the Euclidean layers in both the generator and discriminator with hyperbolic layers (Ganea et al, 2018a) with learnable curvature. Lazcano et al (2021) propose hyperbolic variants of the original GAN (Goodfellow et al, 2020), the Wasserstein GAN WGAN-GP (Gulrajani et al, 2017) and conditional GAN CGAN (Mirza & Osindero, 2014).…”
Section: Hyperbolic Gansmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the intuition that images are organized hierarchically, several works have proposed hyperbolic generative adversarial networks (GANs). Lazcano et al (2021) propose a hyperbolic GAN which replaces some of the Euclidean layers in both the generator and discriminator with hyperbolic layers (Ganea et al, 2018a) with learnable curvature. Lazcano et al (2021) propose hyperbolic variants of the original GAN (Goodfellow et al, 2020), the Wasserstein GAN WGAN-GP (Gulrajani et al, 2017) and conditional GAN CGAN (Mirza & Osindero, 2014).…”
Section: Hyperbolic Gansmentioning
confidence: 99%
“…Lazcano et al (2021) propose a hyperbolic GAN which replaces some of the Euclidean layers in both the generator and discriminator with hyperbolic layers (Ganea et al, 2018a) with learnable curvature. Lazcano et al (2021) propose hyperbolic variants of the original GAN (Goodfellow et al, 2020), the Wasserstein GAN WGAN-GP (Gulrajani et al, 2017) and conditional GAN CGAN (Mirza & Osindero, 2014). The paper finds that their best configurations of Euclidean and hyperbolic layers generally improved the Inception Score (Salimans et al, 2016) and Frechet Inception Distance (Heusel et al, 2017) on MNIST image generation, with the best improvements in the GAN architecture.…”
Section: Hyperbolic Gansmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach involves projecting Euclidean features onto the hyperbolic space in the task heads and designing loss functions based on hyperbolic geometry. Such simple hybrid architectures have been proven effective in various computer vision tasks like recognition [15,20,28], segmentation [1,18], reconstruction/generation [25,31,34,36,40], and metric learning [10,46]. However, Guo et al [15] have shown that learning a mixture of Euclidean and hyperbolic features can exacerbate gradient vanishing, and it remains unclear whether these hybrid models can fully exploit the properties of hyperbolic geometry.…”
Section: Related Workmentioning
confidence: 99%
“…Space of hyperbolic geometry is in fact, just the place we live in, as indicated by the special relativity with multi-layered, hierarchical and multiplex-correlated way. The most characteristic feature about the hyperbolic space against other types of space is that it best represents the data with hierarchical structure (Lazcano et al, 2021), as in deep neural network implemented in deep learning (Peng et al, 2021). Prior research about embedding into non-Euclidean spaces also reports the hyperbolic space as the matching geometry to embed tree-like structures, employing the least distortion (Gu et al, 2018;Sala et al, 2018).…”
Section: The Geometry Of the Brain Networkmentioning
confidence: 99%